If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(w-1)-9=-2(-9w+8)-9w
We move all terms to the left:
5(w-1)-9-(-2(-9w+8)-9w)=0
We multiply parentheses
5w-(-2(-9w+8)-9w)-5-9=0
We calculate terms in parentheses: -(-2(-9w+8)-9w), so:We add all the numbers together, and all the variables
-2(-9w+8)-9w
We add all the numbers together, and all the variables
-9w-2(-9w+8)
We multiply parentheses
-9w+18w-16
We add all the numbers together, and all the variables
9w-16
Back to the equation:
-(9w-16)
5w-(9w-16)-14=0
We get rid of parentheses
5w-9w+16-14=0
We add all the numbers together, and all the variables
-4w+2=0
We move all terms containing w to the left, all other terms to the right
-4w=-2
w=-2/-4
w=1/2
| 14.4=10x+19 | | 12x-30+3=180 | | 7+2x=99 | | 4x/9=-81 | | ||x-2|-1|=1 | | U1=3n-2 | | (6x+5)+90+(11x)=180 | | -119=7(3h+1) | | (6x+5)+95+(11x)=180 | | (2x+16)=3x-12) | | 38-8x=42 | | n-12=31 | | 4m=3+3m | | 29.4=4.2f | | –4n=–6n+8 | | y/2.2=3 | | 25–6b=55 | | C(x)=0.06x+15.75= | | 2.3+m=4.5 | | 0=2y-2y | | 2(x*3-6)=18 | | 5(y+2/5)=15 | | 3h+8=–h | | 9-n=7. | | 4-x/5=4x+6/2 | | C(Q)=((q^2)/6)+2q+10 | | x2+4x+10=5x+30 | | 93=186-u | | w+12=-3 | | -w+262=106 | | 25+0.17x=16.84 | | -3x+9-2x=-12-5x−3x+9−2x=−12−5x |